Influence of Sand Casting Waste as Substitutor of Quartz Sand in Mortar - Prasetya, Fandi Angga; Faria, Niswatun; Susanto, Tri Eddy; Firdaus, Rizqi Ni’amul; Zamzami, Yaski Achmad (Universitas Trunojoyo Madura, 2021)
Sand casting waste has the potential to replace quartz sand in mortar manufacture because it contains high silica. This study uses sand casting waste from the steel industry in Gresik, Indonesia to observe how it affects the quality of the mortar. Initial characterization were carried out to determine the properties of the material, including; magnetic test which results are not attracted by magnets, moisture content test with a value of 0.328%, XRD test to determine the crystallinity content which results contain 99.52% Silica Quartz, and XRF test to determine the content of the compound in which results are 81.25% Silica dominant. Then observations were made by making mortar with the replacement of quartz sand by sand casting with variations of 0% wt, 25% wt, 50% wt, and 100% wt and then tested its compressive strength at 3 days, 7 days, and 28 days. Based on the research that has been done, the optimum result using sand casting is at 25% wt with a compressive strength of 251.15 kgf/cm2 at 28 days of age which is higher than the standard.